Penegakan Hukum dalam Mengungkap Kasus Tindak Pidana Penipuan melalui Media Internet: Studi di POLRES Metro Kota Depok - Harunullah, Alvian; Gunawan, Yusuf (Neolectura, 2023)
This research aims to assess how investigation and law enforcement are used to uncover cases of fraud committed via electronic media. This research was conducted at the Depok Metro Police. This research applies qualitative methods in its process with a focus on empirical research. Data collection was carried out through primary data sources and secondary data. Primary data was collected through interviews with investigators, while secondary information was obtained through the use of books and scientific publications. journals. The research results show that investigators at the Depok Metro Police face several obstacles in tracking fraud perpetrators via electronic media. These obstacles include difficulties in tracking criminals because they often use fake identities, obstacles in accessing perpetrators' account identity information because of the bank's bureaucratic process which takes quite a long time, as well as the lack of a special unit that handles fraud cases using electronic media and a lack of adequate equipment. to carry out searches for criminals using electronic media.